Investigation of Radiation Protection Measures in Extracorporeal Shock Wave Lithotripsy Facilities: A Study Based on NCRP Report 147 - Margaretha, Angelica; Adhianto, Dwi; Manik, Josua Timotius (Diponegoro University Semarang Indonesia, 2024)
Fluoroscopy, also referred to as the C-Arm, is a direct imaging modality used in interventional radiology. It is commonly used, particularly in Extracorporeal Shockwave Lithotripsy (ESWL) for kidney stone removal. The process of kidney stone destruction typically spans from 45 to 60 minutes. Continuous exposure to the radiation can lead to an accumulation of radiation dosage, potentially causing harmful effects. Radiation shielding is one of the most important factors for radiation protection in obtaining a license to construct a radiation room. Radiation shielding requires a minimum thickness to prevent exposure to radiation from escaping the room and posing a risk to the public. Measurements were conducted within the ESWL facility situated at XYZ private hospital, encompassing both internal and external locations, spanning across a total of 11 designated measurement points. The calculations were performed in accordance with the guidelines stated in NCRP Report No.147. The result obtained were 1.665; 1.681; 1.686; 1.109; and 1.716 mm for lead material thickness and 223.8; 225.9; 226.4; 153.2; and 230.2 mm for concrete material thickness. The hospital walls were constructed using concrete with a thickness of 200 mm and were additionally covered with a 2 mm Pb coating. In conclusion, the lead installed meets NCRP standards, but the thickness of the concrete walls around the room still falls short of the requirements.